2019
DOI: 10.1186/s41747-019-0123-4
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of thigh muscle fat infiltration with isometric strength measurements based on chemical shift encoding-based water-fat magnetic resonance imaging

Abstract: BackgroundAssessment of the thigh muscle fat composition using magnetic resonance imaging (MRI) can provide surrogate markers in subjects suffering from various musculoskeletal disorders including knee osteoarthritis or neuromuscular diseases. However, little is known about the relationship with muscle strength. Therefore, we investigated the associations of thigh muscle fat with isometric strength measurements.MethodsTwenty healthy subjects (10 females; median age 27 years, range 22–41 years) underwent chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 47 publications
0
45
0
1
Order By: Relevance
“…Previous studies have shown that fat infiltration can be observed in thigh muscles due to diseases such as neuromuscular and metabolic disorders or age-related muscle atrophy (sarcopenia) [1][2][3][4]. More importantly, the degree of intramuscular fat infiltration serves as a marker for disease severity and progression [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that fat infiltration can be observed in thigh muscles due to diseases such as neuromuscular and metabolic disorders or age-related muscle atrophy (sarcopenia) [1][2][3][4]. More importantly, the degree of intramuscular fat infiltration serves as a marker for disease severity and progression [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, they increased the range of the knee joint and the recovery function of the lower limbs. 35 The range of the knee joint and the strength of the surrounding muscles are increased through progressive resistance exercises and long-term continuous stretching of the joint muscle. These exercises can prevent contracture adhesion, maintain the range of joint motion, gradually improve the stability and prevent the formation of DVT in the lower limbs.…”
Section: Discussionmentioning
confidence: 99%
“…In einer Studie über paraspinale Muskulatur war die altersbedingte FF-Zunahme unabhängig von der Veränderung des Muskelvolumens [62]. In jüngeren Frauen und Männern war aber sowohl am Oberschenkel als auch in der paravertebralen Muskulatur FF nur mäßig mit Muskelkraft (r ≈ 0,5) assoziiert [63,64]. Durch körperliches Training konnte in jüngeren und älteren Männern sowohl FF als auch IMAT des Oberschenkels signifikant verringert werden [65].…”
Section: D-bildgebung Mit Mrtunclassified